Pengaruh level gliserol dalam pengencer tris-kuning telur terhadap kualitas spermatozoa Babi Landrace - Jaimun, Damiana Mutiara; Petrus Kune; Ni Made Paramita Setyani; Kirenius Uly (Agrivet : Jurnal Ilmu-Ilmu Pertanian dan Peternakan (Journal of Agricultural Sciences and Veteriner), 2024)
This study aimed to determine the effect of glycerol (GLY) levels in tris-egg yolk (T-EY) diluent on the quality of landrace boar spermatozoa. The research material was fresh semen from one landrace boar aged two years and two month. The design used was a completely randomized design (RAL) consisting of five treatments and five replications, namely: T0= T-EY, T1=T-EY + GLY 1%, T2= T-EY + GLY 2%, T3= T-EY +GLY 3%, T4=T-EY + GLY 4%. Research variables included motility, viability, abnormalities, and survival of spermatozoa.  The data obtained were analized by the analysis of variance test (ANOVA one way) and further tested with the Duncan Multiple Range Test (DMRT). The results showed that T2 and T3 treatment resulted in statistically higher spermatozoa quality (p<0.05) than other treatments with motility was: 61.00±4.18% and 60.00±3.53%, viability 66.00±4.18% and 63.00±3.53% and survival spermatozoa 56.80±1.09 and 55.20±1.78 hours. It can be concluded that the addition 2% and 3% of glycerol (GLY) in tris-egg yolk (T-EY) diluent gaves a good response in maintaining the quality of Landrace Boar spermatozoa.